Application of cell-derived exosomes in the hematological malignancies therapy - Ghaffari, Kazem; Moradi-Hasanabad, Amin; Sobhani-Nasab, Ali; Javaheri, Javad; Ghasemi, Ali (Frontiers in Pharmacology, 2023)
Exosomes are small membrane vesicles of endocytic origin that are produced by both tumor and normal cells and can be found in physiological fluids like plasma and cell culture supernatants.They include cytokines, growth factors, proteins, lipids, RNAs, and metabolites and are important intercellular communication controllers in several disorders. According to a vast amount of research, exosomes could support or inhibit tumor start and diffusion in a variety of solid and hematological malignancies by paracrine signaling. Exosomes are crucial therapeutic agents for a variety of illnesses, such as cancer and autoimmune diseases. This review discusses the most current and encouraging findings from in vitro and experimental in vivo research, as well as the scant number of ongoing clinical trials, with a focus on the impact of exosomes in the treatment of malignancies. Exosomes have great promise as carriers of medications, antagonists, genes, and other therapeutic materials that can be incorporated into their core in a variety of ways. Exosomes can also alter the metabolism of cancer cells, alter the activity of immunologic effectors, and alter non-coding RNAs, all of which can alter the tumor microenvironment and turn it from a pro-tumor to an anti-tumor milieu. This subject is covered in the current review, which also looks at how exosomes contribute to the onset and progression of hematological malignancies, as well as their importance in diagnosing and treating these conditions.